Dampak Kebijakan Fiskal Terhadap Pertumbuhan Ekonomi Kabupaten Ngawi - Lina Sugiyanto; Sumiati Sumiati (Dinasti Research, 2024)
The focus of this research is to analyze the impact of fiscal policy on economic growth in ngawi district, both in terms of deflation and inflation. To achieve this goal, a simultaneous model was built using the Error Correction Model (ECM) technique. data in this study from various sources such as Bank Indonesia, the Central Bureau of Statistics, and the Ministry of Finance. The findings show that fiscal policy as measured by local revenues, local expenditures and local financing, both in terms of policy and practice, has a significant impact on local economic growth.Based on the results of the analysis, the variable that most affects local economic growth is local revenue. Therefore, the government should maximize the total GDP potential of a region, including from the public and private sectors. The findings of this study support the Harrod-Domar theory which states that the most important factor in achieving good economic growth is to minimize debt.